2006
DOI: 10.1016/j.pec.2005.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for aging: Development, feasibility and preliminary results of an educational program for midlife and older based on proactive coping theory

Abstract: Objectives: This article describes the development, content, feasibility and first results of a short educational program for preparing for aging, based on the process model of proactive coping [Aspinwall LG, Taylor SE. A stitch in time: self regulation and proactive coping. Psychol Bull 1997; 121: 417-36]. The aim of the program is to increase proactive competencies and improve proactive orientations and behaviour. The program consists of four-weekly meetings with 8-10 participants and is given by trainers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
8

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 24 publications
2
32
0
8
Order By: Relevance
“…A recent intervention study was designed by Bode, De Ridder, and Bensing (2006), which is the first study that examined to what extent middle-aged and older people between 50 and 75 years old may be capable of learning to use proactive coping. It demonstrated that a minimal intervention program of four meetings is enough to change the 68 individuals' proactive coping competencies.…”
Section: Clinical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent intervention study was designed by Bode, De Ridder, and Bensing (2006), which is the first study that examined to what extent middle-aged and older people between 50 and 75 years old may be capable of learning to use proactive coping. It demonstrated that a minimal intervention program of four meetings is enough to change the 68 individuals' proactive coping competencies.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…It demonstrated that a minimal intervention program of four meetings is enough to change the 68 individuals' proactive coping competencies. Not only proved their program "In anticipation of the golden years" to be successful in learning its participants to employ proactive coping, it was also regarded by the participants as appealing and highly feasible (Bode et al, 2006).…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Stevens 2001). Relatively few interventions are designed to explicitly focus on the achievement and maintenance of overall wellbeing in later life, by teaching preventive and (pro)active self-management abilities for ageing successfully (for an exception see Bode et al 2005). Therefore, in this paper we aim to contribute to the development of such self-management interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Daarbij is aandacht voor het aanleren van proactieve vaardigheden waarmee problemen in een vroeg stadium voorkomen kunnen worden. (Bode et al, 2006). Effecten op depressie zijn in deze studie niet gemeten.…”
Section: Groepscursus 'Op Weg Naar De Gouden Jaren'unclassified